Peningkatan Karakteristik Islam pada Peserta Didik dalam Program Dzikir Pagi dan Madrasah Mengaji di MAN 1 Ternate - M. Bahtiar Tahir (Universitas Palangka Raya, 2023)
MAN 1 Ternate is an Islamic educational institution, so the implementation of character education is one of the important things in the institution, especially Islamic characteristics. The programs carried out are morning dhikr and madrasah mengaji which are always carried out every day before students enter the classroom. This study aims to analyze the implementation of the morning dhikr and madrasah mengaji programs in improving the Islamic characteristics of students at MAN 1 Ternate. The type of research is qualitative. Data collection techniques used are observation, interviews, and documentation. Data analysis techniques consist of data collection, categorization, and verification. As an Islamic-based educational institution, MAN 1 Ternate implements various programs to form Islamic character, one of which is through morning dhikr and madrasah mengaji activities. The morning dhikr program is carried out every morning before learning begins with the aim of calming the heart and building a positive spirit through reminders of the name of Allah. Meanwhile, madrasah mengaji aims to deepen students' understanding in reading the Qur'an. The results of the study showed that both programs contributed significantly to improving student discipline, strengthening spiritual and moral values, and building a social attitude that cares about others. These programs also help students to be more disciplined, responsible, and have noble morals. Overall, the implementation of morning dhikr and madrasah mengaji at MAN 1 Ternate has proven effective in forming a strong Islamic character in students, creating a better generation, and getting closer to Allah SWT.